2004
DOI: 10.1097/01.ede.0000134865.74261.fe
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Acute Myocardial Infarction

Abstract: Aerobic physical activities such as exercise or walking at work seemed to reduce the risk of MI, whereas anaerobic activities such as heavy lifting at work were related to increased risk of MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(34 citation statements)
references
References 96 publications
(129 reference statements)
2
28
1
3
Order By: Relevance
“…In line with our statement, Petersen et al have noticed that occupational lifting of heavy loads by men, particularly among those with low total occupational and leisure-time physical activity, increased the cardiovascular risk [21]. Although some publications have reported a protective effect of occupational activity on the myocardiac infarction risk [22,23], the latest publications of Holtermann et al…”
Section: Physical Activity and Cardiovascular Mortality O R I G I N Asupporting
confidence: 83%
“…In line with our statement, Petersen et al have noticed that occupational lifting of heavy loads by men, particularly among those with low total occupational and leisure-time physical activity, increased the cardiovascular risk [21]. Although some publications have reported a protective effect of occupational activity on the myocardiac infarction risk [22,23], the latest publications of Holtermann et al…”
Section: Physical Activity and Cardiovascular Mortality O R I G I N Asupporting
confidence: 83%
“…The different types of activity carried out at work might partly explain these inconsistent findings. For example, Fransson et al [46] found that walking and standing at work, both aerobic activities, decreases the risk of myocardial infarction, while lifting or carrying at work increases the risk of myocardial infarction. The relation between all aspects of occupational PA and health should be investigated further.…”
Section: Discussionmentioning
confidence: 99%
“…Według definicji Światowej Organizacji Zdrowia (World Health Organization -WHO) całkowita aktywność fizyczna obejmuje również pracę w domu i ogrodzie oraz aktywność wykonywaną w drodze do pracy, a także w pracy zawodowej. Jak pokazują dane literaturowe, w przypadku tej ostatniej korzyści wynikające z jej podejmowania nie zawsze są oczywiste [6,7].…”
Section: Wstępunclassified
“…Udowodniono m.in jego wpływ na zwiększenie ryzyka zawału mięśnia sercowego [6] czy zgonu z powodu choroby niedokrwiennej serca [7].…”
Section: Wstępunclassified